2006
DOI: 10.1152/ajplung.00341.2005
|View full text |Cite
|
Sign up to set email alerts
|

Zinc modulates airway epithelium susceptibility to death receptor-mediated apoptosis

Abstract: The accelerated loss of lung epithelium through activation of extrinsic apoptosis is believed to play a causative role in lung pathogenesis. Previous investigations have shown that zinc is required to sustain lung epithelial cell viability under stress conditions and that depletion of intracellular zinc predisposes cells to apoptosis. In this investigation, we determined whether intracellular zinc deficiency enhanced the susceptibility of primary, differentiated cultures of human lung epithelium to death recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 22 publications
3
41
0
Order By: Relevance
“…Our results show that PI 3-kinase, NADPH oxidase and NO synthase seemed to be involved both in actin glutathionylation and protein carbonylation in haemocytes exposed to Cd. Activation of PI 3-kinase by Cd has also been reported in previous studies (Kim et al, 2000;Eom et al, 2001;Ostrakhovitch et al, 2002;Bao and Knoell, 2006). Since, PI 3-kinase has been proposed as a survival signal in mild oxidative stress (Konishi et al, 1999;Sonoda et al, 1999;Shimamura et al, 2003), we could hypothesize that NADPH oxidase and NO synthase activation may be a result of PKC and PI 3-kinase activation after Cd exposure in haemocytes of mussels.…”
Section: Discussionsupporting
confidence: 75%
“…Our results show that PI 3-kinase, NADPH oxidase and NO synthase seemed to be involved both in actin glutathionylation and protein carbonylation in haemocytes exposed to Cd. Activation of PI 3-kinase by Cd has also been reported in previous studies (Kim et al, 2000;Eom et al, 2001;Ostrakhovitch et al, 2002;Bao and Knoell, 2006). Since, PI 3-kinase has been proposed as a survival signal in mild oxidative stress (Konishi et al, 1999;Sonoda et al, 1999;Shimamura et al, 2003), we could hypothesize that NADPH oxidase and NO synthase activation may be a result of PKC and PI 3-kinase activation after Cd exposure in haemocytes of mussels.…”
Section: Discussionsupporting
confidence: 75%
“…The reversal of cell proliferation at various Zn 2þ concentrations might be influenced by differences in cell types, marker indices, or experimental conditions (serum-free media; in vivo vs. in vitro), but it might also result from different mechanisms being activated by different concentrations of Zn 2þ . Extracellular zinc activates the PI3K/Akt pathway in many cell types (Bao and Knoell, 2006;Walter et al, 2006;Min et al, 2007), and in our previous study, this activation increased CDK protein levels and […”
Section: Discussionmentioning
confidence: 60%
“…In a prospective study, preventive zinc supplementations to all age groups (infants, pre-schoolers and older prepubertal children) showed a 6% non-significant reduction in mortality due to all causes. 21 Prospective studies specifically on risk of incidence of ARIs in young children in developing countries have shown that routine zinc supplementation reduced them. 22,23 These studies were done to assess the association between respiratory morbidity and zinc in children.…”
Section: Discussionmentioning
confidence: 99%